Developing Reading Handbook Based on Genre Based Approach for Islamic Senior High School Level - Kholifatur Rosyida; rasyidah nur aisyah (Jurnal Pendidikan (Teori dan Praktik), 2019)
The purpose of the study was intended to develop supplementary reading material based on genre text for students in the tenth grade of Senior High School in order to help the learners in comprehending and interesting to study about Islamic story. This research was conducted by validation product by the experts, and try out. This research showed that the validation product by the experts showed 80% the product was appropriate, and the try out by the students were more than expected interval (l00%-76%). To find out whether the effective of the product, the writer gives the students pretest before implementing the product and posttest after implementing. The finding shows that the t-test calculation from the result of pre-test is 23% and post-test which on  is 80,7%. The result of this study concluded that the product was effective to use.